Gestão estratégica de negócio e as tecnologias de informação: o caso do gerenciador financeiro do Banco do Brasil - Almeida Filho, Orlando de [UNESP] (2009)
This study investigates and analyzes the flow of information between the Bank of Brazil (Agency Houses of Campo Grande, Mato Grosso do Sul) and their corporate clients to identify strategic alignment between business management and information technology (IT), using the Application Manager service (GEFIN). The issues focus of this study are to examine whether: The banking sector, which employs the concept of strategic planning effectively, using a comprehensive approach to IT with the business strategy? How the subjects users of these technologies use the information to obtain greater efficiency to their business plans? Accordingly, my view of the research process we adopted the strategy on quality. The research method to achieve the proposed objectives was the case study. As instruments of data collection were applied a questionnaire to the customers who use the PJ GEFIN application and interview members of the portfolio PJ (Actual Position, Assistant Business Manager and Accounts). The central idea was to compare and clearly need these to see if indeed the technological tool allows GEFIN smoothly dialogue between the customer and the Bank of Brazil. The survey results made it possible to see that it is imperative to the Bank of Brazil, which make up a sector highly competitive and dynamic, seeking not only in its technology platform, but also in other organizational tools such as strategic information management, strategic planning business should be aligned to information technologies and best practices in competitive intelligence organization, guided by new ways of thinking about strategic management of business more broadly.